Study on Organic Redox Flow Battery Mechanism using TEMPO and FMN-Na Solutions - Faishal Maulana Kusumah; Dita Baeti Pridiana; Peter Kusnadi; Dessy Ariyanti (Dept. of Chemical Engineering, Diponegoro University, 2019)
Among numerous energy storage technologies, redox flow battery is one of the promising technologies that can be used to supply reliable continuation of electricity to electricity grids with a scale up to MW or MWh. In this paper, the process mechanism and optimization of redox flow battery using organic solution such as Riboflavin-5’-phosphate sodium salt dihydrate (FMN-Na) as anolyte and 4-hydroxy-2,2,6,6-tetramethylpiperidin-1-oxyl (TEMPO) as catholyte were investigated. Sodium and chloride ions in salt feed were moved respectively to anolyte and catholyte by electrochemical reaction of electrolytes during the charge process and return to the feed during the discharge process. The study was carried out by given electric current with different voltage to graphite electrode range 1,5-10,5 volts and TEMPO concentration 0,02-0,08 M. The result shows that the optimum voltage is 7,5 volts with the concentration of TEMPO 0,06 M. The result also confirms the role of TEMPO solutions in the cathode. In addition to that, the FTIR and SEM analysis to the sedimentation generated during the process also revealed the change of the anolyte and catholyte after charging process.Keywords: Organic; Flow Battery; TEMPO; FMN-Na; energy storage